STRUCTURE OF MIXED HOLM-OAK (QUERCUS-ILEX) ALEPPO PINE (PINUS-HALEPENSIS) FORESTS IN NORTHEASTERN SPAIN - Espelta, J. M.; GENE, C.; Retana, J.; TERRADAS, J. (RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES, 1992)
Mixed forests of Aleppo pine (Pinus halepensis) and holm-oak (Quercus ilex) cover a great part of Northeastern Spain. Nevertheless, little is known about their structure, dynamics and regeneration. For some years, a research group in CREAF has collected data about those aspects, in order to use them to develop models that could be used as a tool for forest management. Previous results obteined about the structure of these stands are presented in the present paper.
The following values have no corresponding Zotero field: periodical: RESPONSES OF FOREST ECOSYSTEMS TO ENVIRONMENTAL CHANGES pub-location: BARKING ESSEX
Keywords: mixed forests; Pinus halepensis; Quercus ilex; Spain